Re-evaluating our focus in addiction: emotional dysregulation is a critical driver of relapse to drug use - Lexi J. Hand; Louise M. Paterson; Anne R. Lingford-Hughes (Translational Psychiatry)
Abstract Most addiction research has focused on reward- and impulsivity-related neurocircuitry. However, the impact of the withdrawal/negative affect stage in the addiction cycle has been somewhat overlooked, despite it being commonly evident in the clinic. This stage crucially drives negative reinforcement of repeated drug use and relapse, yet less is known about its neural underpinnings. How negative emotional processing is dysregulated in substance dependence is incompletely understood and may manifest differentially across the types of substances. In turn, the regions involved in negative emotional processing may show different patterns of dysregulation. Understanding how neurocircuitry involved in negative states differs across various substances may help inform new targets for treatments. Following a comprehensive literature search of studies examining negative emotional processing in substance dependence, a quantitative approach was deemed inappropriate. Instead, we employed a narrative approach to exploring neural responses to tasks involving emotional processing in alcohol, cocaine, opioid and cannabis dependence. Regions that were found to be dysregulated included the amygdala, insula, anterior cingulate, and medial prefrontal cortex. However, patterns of reactivity differed across alcohol, cocaine, opioid and cannabis dependence. Brain activation in alcohol dependence broadly appeared blunted in response to negative affective stimuli and emotional faces, whilst conversely appeared heightened in cocaine dependence. In opioid dependence, the amygdala was consistently implicated, whilst the insula, anterior cingulate, and medial prefrontal cortex were implicated in cannabis dependence. However, there was wide variability amongst the studies, with very few studies investigating opioid and cannabis dependence. These findings suggest emotional dysregulation varies according to the type of substance dependence. However, the variability in findings and lack of studies highlights the need for more research in this area. Further characterisation of emotional dysregulation in substance dependence will enable identification of treatment targets. More targeted treatments that modulate negative emotional processing could substantially improve outcomes by aiding relapse prevention.